2012
DOI: 10.1162/jocn_a_00160
|View full text |Cite
|
Sign up to set email alerts
|

Visuomotor Coordination and Motor Representation by Human Temporal Lobe Neurons

Abstract: The division of cortical visual processing into distinct dorsal and ventral streams is a key concept in primate neuroscience [Goodale, M. A., & Milner, A. D. Separate visual pathways for perception and action. Trends in Neurosciences, 15, 20-25, 1992; Steele, G., Weller, R., & Cusick, C. Cortical connections of the caudal subdivision of the dorsolateral area (V4) in monkeys. Journal of Comparative Neurology, 306, 495-520, 1991]. The ventral stream is usually characterized as a "What" pathway, whereas the dorsa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 74 publications
(72 reference statements)
4
31
3
Order By: Relevance
“…Only processing speed correlated with aberrant rs-fMRI activity within the salience network (including the planum temporale) using ICA. This finding converges with increasing evidence that visuomotor coordination and motor representation are modulated by neurons within the temporal region (Tankus and Fried, 2012) and that cognitive processing speed is associated with temporal cortical structural integrity (Turken et al, 2008). Moreover, some data suggest that higher stages of language processing operate at a fixed speed and could theoretically impose a 'temporal bottleneck' on language functions (Vagharchakian et al, 2012).…”
Section: Discussionsupporting
confidence: 84%
“…Only processing speed correlated with aberrant rs-fMRI activity within the salience network (including the planum temporale) using ICA. This finding converges with increasing evidence that visuomotor coordination and motor representation are modulated by neurons within the temporal region (Tankus and Fried, 2012) and that cognitive processing speed is associated with temporal cortical structural integrity (Turken et al, 2008). Moreover, some data suggest that higher stages of language processing operate at a fixed speed and could theoretically impose a 'temporal bottleneck' on language functions (Vagharchakian et al, 2012).…”
Section: Discussionsupporting
confidence: 84%
“…A promising research area in that respect is constituted by visuo-motor coordination tasks. Indeed, in a recent study [37] the authors found two populations of context-independent and context-dependent in the mediotemporal (MT) lobe. The first neural population encodes information about the position, the speed, and the acceleration of the hand irrespectively from the context, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…2.4.3 and 2.5, many aspects affect the quantity and quality of tasks assigned to each stream in a given condition. In most cases the work partition between the streams is rather progressive, depending for example on task, action delay or on object familiarity (Sugio et al 2003b;Himmelbach and Karnath 2005;Cohen et al 2009;Tankus and Fried 2012;Wokke et al 2014). An explanation for this last case is that contribution of the ventral stream on the formation of the grip is modulated by the confidence achieved by the LOC in the recognition of the target object.…”
Section: Role Of the Dorsal And Ventral Streams And Possible Interactmentioning
confidence: 99%